Differential inhibition by trifluoperazine of responses of hippocampal CA1 pyramidal cells to NMDA and AMPA in vivo - Budai, Dénes (Acta Biologica Szegediensis, 2011)
The effects of trifuoperazine (TFP), a phenothiazine neuroleptic drug having potent anticalmodulin activity, were studied on the responses of hippocampal CA1 pyramidal cells to N-methyl-D-aspartic acid (NMDA) and (RS)-A-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) in vivo. Single-unit activity was recorded using multibarrel carbon fiber containing microelectrodes whilst all drugs were delivered by microiontophoresis. NMDA and AMPA were iontophoresed alternately so that they evoked comparable responses in terms of peak heights as peristimulus time histograms were recorded. We observed that changing the stimulation intensity of one classes of receptors (e.g. NMDA) greatly influenced the responsiveness of the other (e.g. AMPA) and vice versa. In the presence of iontophoretically applied TFP responses to both NMDA and AMPA were significantly decreased. More interestingly, NMDA-evoked responses were significantly more inhibited by TFP than responses to AMPA under the same experimental conditions. In our conclusions, these results are due to the inhibition by TFP of the second messenger cascade events leading from NMDA receptors via Ca2+/calmodulin to AMPA receptors and, in consequence, for the blocking of phosphorylation of AMPA receptors and their sensitization. It is also likely that the function of NMDA receptors by itself is, at least in part, dependent on the Ca2+/calmodulin-mediated events.